EFFECT OF USING STYLES RANDOM AND BLOCKED PRACTICE IN LEARN GOALING AND PASSING IN SKILLS IN FOOT BALL - Subhi, Mustafa (Journal of Physical Education, 2010)
Chapter one This chapter includes the introduction which talks about importance of early learning the importance of research in choose styles of learning simplified mission student. These styles in random and blocked practice Aims: 1. Knowlege which the best style in learn goaling skill 2. Knowledge which the best style in learn passing skill. Chapter two This chapter contained the theory studies that contained learning style, goaling and passing skills. Chapter three This chapter contained on searching monologue which used(tribulation search) and sample search which contained on (20) students of intermediate youth school which divided in to two group every group contained(10) students used for testing of bending use and testing to the sure of same between the two groups procedures to experimental and correct results by using colleting ways . Chapter four This chapter contained on giving the results of testing of goaling and passing skills and analyzing then discussing then by grouping the results after the first and the last check . Chapter five This chapter contained resulting and given are which the researcher reached with the results the best of these results are. 1. The best using the style random practice in learn goaling skill. 2. The best using the style blocked practice in learn passed skill